2021
DOI: 10.1002/ijgo.13572
|View full text |Cite
|
Sign up to set email alerts
|

Role of first‐trimester three‐dimensional (3D) power Doppler of placental blood flow and 3D placental volume in early prediction of pre‐eclampsia

Abstract: Objective To assess the efficacy of first‐trimester three‐dimensional (3D) placental volume as well as 3D power Doppler of placental vascular indices for early prediction of pre‐eclampsia. Methods The prospective cohort study included over 2019 women with a singleton pregnancy in their first trimester at 11–13+ weeks of pregnancy. All women were examined by 3D abdominal ultrasound, including Doppler techniques for the placental volume and placental vascular indices. Uterine artery Doppler indices were also ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 46 publications
0
5
1
Order By: Relevance
“…Previous studies report significantly lower VI, FI, and VFI in the first and second trimester in the PE group 10,11 . However, we found no significant differences in VI, FI, and VFI in the third trimester, possibly because, in the first and second trimesters, IBV had not yet developed to accurately represent the ischemic state of IS.…”
Section: Discussioncontrasting
confidence: 87%
See 2 more Smart Citations
“…Previous studies report significantly lower VI, FI, and VFI in the first and second trimester in the PE group 10,11 . However, we found no significant differences in VI, FI, and VFI in the third trimester, possibly because, in the first and second trimesters, IBV had not yet developed to accurately represent the ischemic state of IS.…”
Section: Discussioncontrasting
confidence: 87%
“…21 Previous studies report significantly lower VI, FI, and VFI in the first and second trimester in the PE group. 10,11 However, we found no significant differences in VI, FI, and VFI in the third trimester, possibly because, in the first and second trimesters, IBV had not yet developed to accurately represent the ischemic state of IS. In the third trimester, IBV and erythrocyte count increased as a compensatory response of the fetus to IS ischemia, and it is likely that the VI, FI, and VFI values did not decrease despite placental circulatory failure.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…However, the ultrasound imaging of the placenta is rather unsatisfactory in the first trimester. 3D-PDU showed a high sensitivity in visualization of villous blood vessels in placenta and even distal branches, providing information about vascular density, diameter change, and curvature and calculating three vascular indexes such as VI, FI, and VFI in the form of a histogram to achieve the quantitative evaluation of blood vessel density and blood perfusion in the placenta [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus the applicability of placental volume assessment alone as an early predictor of preeclampsia severity of is limited benefit. In another study, Abdallah et al (14) revealed that women who develop preeclampsia had a significantly lower placental volume than normotensive women. During the first trimester of the study mentioned above, the placental volume was estimated.…”
Section: Discussionmentioning
confidence: 95%